Penerapan Hukum terhadap Pelaku dan Korban Tindak pidana Obstruction of Justice - Tangko, Lidwina Aprilliana Allo; Agung, Dirga; Andi Dewi Pratiwi (Alauddin Law Development Journal (ALDEV), 2023)
Obstruction of Justice is an act classified as a criminal offense because it obstructs or hinders the legal process in a case. Lawyers in carrying out their professional duties are often associated with allegations of obstructing the legal process in cases involving their clients. The purpose of this writing is to understand the legal regulations regarding obstruction of justice in Indonesia and the characteristics of lawyer's conduct that can be classified as obstructing the legal process or obstruction of justice. The method used in this article is juridical normative. The research findings indicate that obstruction of justice is generally regulated in Article 221 of the Indonesian Criminal Code (KUHP) and specific legislation. A lawyer can lose their immunity and be considered to have committed obstruction of justice if such conduct is not based on good faith and unrelated to their professional duties.